Model Pembelajaran Inklusif Anak Usia Dini Berkebutuhan Khusus (ABK) Berbasis Parenting pada Keluarga di Kota Metro - Siti Alawiyah; Muhammad Yusuf; Ferdian Utama; Yuli Supriani (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2026)
This study aims to describe a parenting-based inclusive early childhood learning model in families in Metro City. The study used a qualitative approach with field research, with parents of children with special needs such as ADHD, dyslexia, and speech delay as subjects. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation, while data analysis used the interactive model of Miles and Huberman. The results showed that the parenting-based inclusive learning model was implemented through five main stages: identification and assessment of children's needs, adjustment of learning materials and activities, implementation of educational play activities, active involvement of parents as companions, and periodic evaluation and adjustment. The learning process takes place flexibly, naturally, and is based on daily experiences within the family, with parents as the primary educators who adjust learning strategies based on the child's conditions and needs. Educational play activities are the main medium in stimulating children's cognitive, social, and language development. Active parental involvement in ongoing mentoring and evaluation is a determining factor in learning success. The research findings indicate that this model is effective in supporting the development of children with special needs, although it still requires strengthening in terms of systematization and professional support for optimal implementation.